Mapping Islamic financial technology publications through bibliometric analysis: A study on the Scopus database - Abdurrahman Mansyur (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2024)
Purpose — This study aims to analyse research trends in Islamic fintech through Co-Authorship, Co-Citation, and Cluster Analysis.Method — This study uses bibliometric analysis techniques on the Scopus database assisted by VOSviewer and Microsoft Excel tools. A total of 220 documents were found to contain the keywords Islamic AND Fintech in the title, abstract, and keywords in the research until July 16, 2023.Result — The study results show that Islamic Fintech is becoming an interesting topic for researchers from various countries, especially Malaysia, Bahrain and Indonesia, which contribute a significant number of publications. The results of the Co-Authorship analysis show that Hassan, M.K. is the author with the highest collaboration of articles, which also indicates the productivity of article publication in Islamic Fintech.Contribution — This research is the first to examine Islamic fintech research trends in the Scopus database. The findings from this study can be important information for developing future research directions to advance this field sustainably.